Do People Adapt to Unemployment? Findings from Türkiye - Zeynep B. Uğur (İstanbul İktisat Dergisi)
Unemployment is known to have adverse effects on well-being. Moreover, people can adapt to many adverse events to some extent. This study seeks to answer the question “Do people adapt to unemployment over time?” to shed light on the happiness of the unemployed in Türkiye. We use individual-level data from the Life Satisfaction Survey in 2010–2020. First, we show that, consistent with previous research, the happiness of the unemployed is significantly lower than that of the employed. Second, those who have been unemployed for less than a year are less happy than those who have been unemployed for more than a year. That is, the unemployed become accustomed to their situation over time. However, those who have found work in the last year are much happier than both the unemployed in general and those who have been unemployed for more than a year and have adapted to unemployment. From the standpoint of happiness, our results support the hypothesis that finding a job is preferable to becoming accustomed to unemployment. In addition, married men are more adversely impacted by unemployment and less adaptive to unemployment.